GENDER INEQUALITY IN CHARLOTTE BRONTE’S JANE EYRE - Monica Wurangian; Agustine Clara Mamentu; Fivy Andries (Program Studi Pendidikan Bahasa Inggris, 2023)
This study aims to reveal gender inequality in Charlotte Bronte’s Jane Eyre. The writer employs a qualitative method in conducting this research. About collecting the data, the writer collected uses primary sources: which is the work of Charlotte Bronte’s Jane Eyre, while secondary sources were references such as journals, books, or internet sources that are related and relevant to the research. Regarding of data analysis, the writer uses the feminist approach was used to analyze inequality in gender. The study shows that Jane Eyre’s life as the main character has experiences inequality which she has to face in her life such as mistreatment from society and men in the novel. She can finally feel happy living with someone she loves. And she no longer felt that she had to be distinguished from the degree of the man who lives with her. The writer wishes that in this research, the reader can learn not to assume that gender inequality is a trivial thing. Because actually, all women have the right to live their lives.